2009
DOI: 10.1002/lsm.20789
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy promotes healing of chronic diabetic leg ulcers that failed to respond to other therapies

Abstract: Combined 660 and 890 nm light promotes rapid granulation and healing of diabetic ulcers that failed to respond to other forms of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
20

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 78 publications
3
104
0
20
Order By: Relevance
“…In addition to increased MMP-9, other studies have also found increased levels of MMP-2 and -8 [4][5][6]. PBM has been shown to stimulate cells and wound healing, and has aided in the healing of chronic diabetic ulcers [8][9][10][11][12][13]. Aparecida Da Silva and co-workers irradiated diabetic induced male Wistar rats (660 nm, 4 J/cm2) and evaluated MMP-2 and -9, and Type I and III collagen 24 h post-irradiation [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to increased MMP-9, other studies have also found increased levels of MMP-2 and -8 [4][5][6]. PBM has been shown to stimulate cells and wound healing, and has aided in the healing of chronic diabetic ulcers [8][9][10][11][12][13]. Aparecida Da Silva and co-workers irradiated diabetic induced male Wistar rats (660 nm, 4 J/cm2) and evaluated MMP-2 and -9, and Type I and III collagen 24 h post-irradiation [25].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to an increase in adenosine triphosphate (ATP) which in turn activates a cascade of intracellular signals and messengers, leading to various down-stream effects such as increased proliferation, cellular migration and viability, collagen production, as well as gene transcription [8]. There are several research papers which demonstrate the beneficial effect of PBM in the treatment of diabetic ulcers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition there is evidence that such techniques may be effective in treating a range of medical conditions including diabetic leg ulcers [159,160], pancreatic cancer [161], etc.…”
Section: Light and Colour As A Therapeutic Modalitymentioning
confidence: 99%
“…Accordingly it is completely unrealistic to expect that the results from clinical studies, based upon an incomplete understanding of the phenomena, can give an optimum physiological response. Nevertheless light-based biofeedback, neurofeedback and laser-based techniques have become widely used for the treatment of a range of conditions including psoriasis, seasonal-affective disorder, hyperbilirubinaemia, dyslexia.In addition there is evidence that such techniques may be effective in treating a range of medical conditions including diabetic leg ulcers [159,160], pancreatic cancer [161], etc.It has taken a great deal of time for the person to become unwell. Accordingly it is unreasonable to expect instantaneous relief.…”
mentioning
confidence: 99%
“…Later, the ima ges were analy zed using the color decon vo lu tion plu gin func tion of the ImageJ soft wa re (US National Institutes of Health, Bethesda, MD, USA), which supplies the per cen ta ge of blue stai ning (col la gen) in each ROI. [18][19][20][21][22] …”
Section: Analysis Of Col La Ge Ne Sismentioning
confidence: 99%